Contextualising teaching. Teaching practice developed by expert teacher educators - Adula Bekele Hunde; Giuseppe Tacconi (Firenze University Press, 2018)
This article examines the way a group of expert teachers' educators contextualises their teaching. To this end, a qualitative phenomenological approach was employed to collect and analyse data from 30 expert teachers' educators. Grounded theory was used to conceptualise and categorise evidences emerged from the analysis of texts while stories of practices were created for each category emerged for illustration. In general, three teaching strategies emerged as means of contextualising teaching: connecting teaching to authentic experiences, aligning practices in teacher education to secondary school teaching and contextualising teaching to students' level of understanding. Lastly, the lesson each university could draw from one another and implications of the study are highlighted. Contestualizzare l'insegnamento. Una pratica sviluppata da esperti formatori di insegnanti L'articolo esplora come un gruppo di esperti formatori di insegnanti utilizzi la strategia della contestualizzazione nel proprio insegnamento. Uno studio qualitativo di taglio fenomenologico è stato realizzato per raccogliere e analizzare dati relativi a 30 formatori di insegnanti in due università. Per la concettualizzazione è stato utilizzato un approccio "grounded" che ha fatto emergere un insieme di categorie dall'analisi dei testi; per ciascuna categoria sono stati selezionati frammenti di narrazione. Sono emerse tre principali articolazioni di tale strategia didattica: connettere l'insegnamento a esperienze autentiche dei partecipanti, allineare le pratiche della formazione degli insegnanti a quelle presenti nella scuola secondaria e contestualizzare l'insegnamento al livello di comprensione degli studenti. In conclusione si evidenzia ciò che, a questo riguardo, ciascuna università può imparare dall'altra.